Duodenal Dieulafoy lesion: a rare and fatal cause of gastrointestinal bleeding - Shumilina, Tetiana; Patricia , Boldizhar; Kochmar, Mykhailo (The Ukrainian Scientific Medical Youth Journal, 2024)
the article summarizes the issue of Dielafoy lesion of the duodenum, as an unusual and rare cause of recurrent gastrointestinal bleeding, which can be fatal. This lesion can occur in various parts of the gastrointestinal tract (GI), most often in the stomach, especially at the level of the lesser curvature; however, it can occur in other parts, including the colon, esophagus, and duodenum. The main goal of this study is to improve the results of diagnosis and treatment of Dielafoy lesions by identifying the nuances of its clinical course and analyzing the use of various types of endoscopic hemostasis in patients with this syndrome. The research used the methods of bibliographic and content analysis of the literature, comparative approach and synthesis, as well as semantic grouping in relation to the features of the course, diagnosis and treatment of the Dielafoy lesion of the duodenum. All documents found on various official websites were analyzed and the collected information was compared and grouped. The relevance of the study is that gastrointestinal bleeding is one of the main problems and causes of mortality in emergency surgery. In the etiology of gastrointestinal bleeding, a number of well-known pathologies are distinguished, such as peptic ulcer disease of the stomach and duodenum, Mallory-Weiss syndrome, neoplasms and varicose veins of the esophagus and stomach. There are also a number of other, rare, but no less dangerous diseases characterized by the development of acute gastroduodenal bleeding. They include Dielafoy lesion - a rare genetic pathology characterized by the abnormal development of blood vessels in the submucosal layer without signs of an inflammatory process, which rupture causes profuse bleeding. Despite the expansion of diagnostic and therapeutic possibilities, the risk of bleeding and its danger for life in the case of damage to the DL is still quite high. Clinical manifestations include painless upper gastrointestinal bleeding, including melena, hematochezia and vomiting or rarely iron deficiency anemia (IDA); however, most patients are asymptomatic. Some patients also have non-gastrointestinal comorbidities such as hypertension, diabetes, and chronic kidney disease (CKD). The diagnosis is made by esophagogastroduodenoscopy (EGD), which includes the presence of micropulsatile jets from the mucosal defect, the appearance of a fresh, densely adherent clot with a narrow point of attachment to a small mucosal defect, and visualization of a protruding vessel with or without bleeding. Initial FGDS may be nondiagnostic due to the relatively small size of the lesion. Other diagnostic methods include endoscopic ultrasound and mesenteric angiography. Treatment of duodenal DL includes thermoelectrocoagulation, local injection of epinephrine, sclerotherapy, bandaging and hemoclips. We present here the case of a 71-year-old woman with a history of severe IBD requiring multiple blood transfusions and intravenous iron and who was found to have a Duodenal Dealfoy lesion. The results of this study may be of interest to primary care physicians, therapists, gastroenterologists, laboratory diagnosticians, endoscopists and surgeons.